A multiresolution approach with method-informed statistical analysis for quantifying lymphatic pumping dynamics - Mohammad S. Razavi; Katarina J. Ruscic; Elizabeth G. Korn; Marla Marquez; Timothy T. Houle; Dhruv Singhal; Lance L. Munn; Timothy P. Padera (npj Imaging)
Abstract Despite significant strides in lymphatic system imaging, the timely diagnosis of lymphatic disorders remains elusive. This is driven by the absence of standardized, non-invasive, reliable, quantitative methods for real-time functional analysis of lymphatic contractility with adequate spatial and temporal resolution. Here, we address this unmet need by integrating near-infrared fluorescence lymphangiography imaging with an innovative analytical workflow that combines data acquisition, signal processing, and statistical analysis to integrate traditional peak-and-valley analysis with advanced wavelet time-frequency analyses. Variance component analysis was used to evaluate the drivers of variance attributable to each experimental variable for each lymphangiography measurement type. Generalizability studies were used to assess the reliability of measured parameters and how reliability improves as the number of repeat measurements per subject increases. This allowed us to determine the minimum number of repeat measurements needed per subject for acceptable measurement reliability. This approach not only offers detailed insights into lymphatic pumping behaviors across species, sex and age, but also significantly boosts the reliability of these measurements by incorporating multiple regions of interest and evaluating the lymphatic system under various gravitational loads. For example, the reliability of the peak-and-valley analysis of human lymphatic vessels was increased 3-fold using the described approach. By addressing the critical need for improved imaging and quantification methods, our study offers a new standard approach for the imaging and analysis of lymphatic function that can improve our understanding, diagnosis, and treatment of lymphatic diseases. The results highlight the importance of comprehensive data acquisition strategies to fully capture the dynamic behavior of the lymphatic system.